Emerging Market Business Cycles : The Role of Labor Market Frictions - Boz, Emine (IMF Working Papers; Working Paper ;, 2012)
Emerging economies are characterized by higher consumption and real wage variability relative to output and a strongly countercyclical current account. A real business cycle model of a small open economy that embeds a Mortensen-Pissarides type of search-matching frictions and countercyclical interest rate shocks can jointly account for these regularities. In the face of countercyclical interest rate shocks, search-matching frictions increase future employment uncertainty, improving workers' incentive to save and generating a greater response of consumption and the current account. Higher consumption response in turn feeds into larger fluctuations in the workers' bargaining power while the interest rates shocks lead to variations in the firms' willingness to hire; both of which contribute to a highly variable real wage.